Effect of cow replacement strategy on cow and calf performance in the beef herd. (11th July 2018) - McCabe, S.; Prendiville, R.; Evans, R.; O'Connell, N. E.; McHugh, N.
Abstract : Two contrasting replacement strategies are used by Irish beef farmers to select replacement females – animals sourced from within the suckler beef herd and sourced from the dairy herd. The objective of this study was to investigate the effect of replacement strategy (i.e. beef v . beef×dairy (BDX)) on cow and calf performance using data from the national beef database across a range of beef and dairy breeds. The association between replacement strategy and calving difficulty score, calving interval, weaning weight, weaning price and all carcass traits was investigated using a mixed model. The effect of replacement strategy on cow survival, calving dystocia and calf perinatal mortality was quantified using logistic regression. Beef cows were older (10.92 days; P <0.001) at their first calving, but were 1.15 times ( P <0.01) more likely to survive to a subsequent lactation compared with BDX cows. Calving interval was 1.53 days shorter ( P <0.001) for BDX compared with beef cows. Greater calving difficulty and calving dystocia was associated with beef cows ( P <0.001) relative to BDX. However, BDX were 1.36 times ( P <0.001) more likely to have a dead calf at birth relative to beef cows. Calves weaned from BDX were heavier (18.49 kg; P <0.001) at weaning, reached slaughter 12.8 days earlier ( P <0.001), had 7.99 kg heavier carcass ( P <0.001) and a greater fat score ( P <0.001) compared with the progeny of beef cows. Beef cow progeny had a superior conformation score (0.5; P <0.001) and achieved a greater price per kilogram ( P <0.001) compared with progeny from BDX. Beef cull cows had a heavier carcass (5.58 kg), superior carcass conformation, greater carcass price per kilogram and greater overall carcass value ( P <0.001) than BDX. Results from this study show that replacement strategy is of fundamental importance depending on the type of system implemented by farmers and consideration must be given to the traits of importance within the context of the individual production system.